Association Between Functional Impairment and Self-Concept in Individuals with Stroke - Hendriana, Yana (Fakultas Kesehatan, Universitas Nurul Jadid, 2024)
Introduction: Stroke is a leading cause of disability worldwide, often resulting in impaired physical function and disrupted self-concept. Extremity weakness, as one of the most common sequelae of stroke, may significantly impact an individual's psychological adjustment. However, the relationship between functional dependency and self-concept remains underexplored in clinical practice. Objectives: This study aimed to investigate the association between functional status and self-concept in individuals recovering from stroke. Methods: A cross-sectional correlational design was employed involving 33 stroke patients selected through non-probability sampling. Functional status was assessed using the Barthel Index, while self-concept was measured with a validated self-concept questionnaire. Statistical analysis was performed using Spearman’s rank correlation test. Results: The majority of patients exhibited total dependency (69.7%) and negative self-concept (60.6%). A significant positive correlation was found between functional status and self-concept (r = 0.578, p = 0.046), indicating that higher functional independence was associated with more positive self-perception. Conclusions: Functional limitations in stroke patients are significantly associated with negative self-concept. These findings suggest the need for holistic rehabilitation strategies that integrate physical and psychological support to optimize recovery and quality of life.